Pelatihan Keterampilan Pembuatan Keripik Kelakai dalam Meningkatkan Kemampuan Berwirausaha Anak Panti Asuhan Ayah Bunda Palangka Raya - Saiffullah Darlan (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
The purpose of this community service is to provide skills to the orphans of the Ayah Bunda Orphanage of Palangkaraya so that after they are no longer fostered at the institution, they have the skills to be able to do entrepreneurship independently and can support themselves. The output is expected to carry out community service so that the orphans, especially those who are teenagers, will be able to be independent and no longer dependent on other people in the community. The method used in carrying out this training is in the form of giving lectures with instructions for making chips; discussion with fellow participants; demonstration, the implementation of training to make Kelakai chips; and evaluation, which is giving value to participants who participated in the training. Based on the evaluation results of the implementation of the training that the participants attended the training very well and gave a very positive response, this can be seen from the results of the evaluation: First, from the five stages of the activity from the preparatory stage, the suitability of making chips, the suitability of the texture, the suitability of the resulting flavor and the stage of arranging equipment after completion of activities. Second, the evaluation results in group 1 category are very good with a score of 18; group 2 good score 16; groups 3 and 4 categories both scored 14 and 15, respectively.